Benefits of Early Learning of English in Preschool and Primary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the benefits of learning English early in kindergarten and primary school. It offers an overview of the cognitive, global, and psychosocial benefits of such training and provides examples of scientific research supporting its effectiveness. The article also looks at practical examples of games and exercises that help develop language skills. Overall, it emphasizes the importance of early English language acquisition for children's future success and development.